Collaboration Governance In Development Of Tourism Objects In Kampar Regency Riau Province - Zainal Zainal; Data Wardana; Muhammad Cahyadi (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
Empirically the problems that occur in this study are the absence of specific regulations regarding the forms, patterns and models of collaboration between the government, private sector and the community in collaborative activities. The research method used is a qualitative research method, with a descriptive approach. Data collection techniques were carried out by means of interviews, observation, and recording of documents related to the collaboration process carried out in the implementation of the tourism object development program in Kampar Regency. The results of the research show that collaborative governance in the development of tourism objects in Kampar Regency has been running since 2019 until now. Based on the results of the research, it can be concluded that the process of collaborative governance in the development of tourism objects in the Village of Koto Mesjid, Kampar Regency, has been effective, which is marked by the stakeholders having carried out their main tasks to the fullest. Even so, there are still a few mistakes in communication that are not going well and the communication that is established is still lacking due to delays in information being obtained by the public.  Keywords: Collaborative Governance, Tourism Object Development, Tourism